2005
DOI: 10.3748/wjg.v11.i21.3197
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloripromote gastric cancer cells invasion through a NF-kB and COX-2-mediated pathway

Abstract: Our data demonstrate that H pylori infection promotes gastric epithelial cells invasion by activating MMP-9 and VEGF expression. These effects appear to be mediated through a NF-kappaB and COX-2 mediated pathway, as COX-2 or NF-kappaB inhibitor significantly attenuate the invasiveness of gastric cancer cells and the expressions of MMP-9 and VEGF protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 27 publications
3
62
0
2
Order By: Relevance
“…Therefore, it is suggested that the stimulatory action of nicotine on invasiveness (migration of cancer cells) and angiogenesis (mobility of endothelial cells) are dependent on COX-2 activity and the angiogenic action of VEGF. This phenomenon is in accord with other study that inhibitor of COX-2 markedly reduces Helicobacter pylori -promoted gastric cancer cell invasion, concomitant with down-regulation of MMP-9 and VEGF protein expressions (39).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is suggested that the stimulatory action of nicotine on invasiveness (migration of cancer cells) and angiogenesis (mobility of endothelial cells) are dependent on COX-2 activity and the angiogenic action of VEGF. This phenomenon is in accord with other study that inhibitor of COX-2 markedly reduces Helicobacter pylori -promoted gastric cancer cell invasion, concomitant with down-regulation of MMP-9 and VEGF protein expressions (39).…”
Section: Discussionsupporting
confidence: 93%
“…This process is carried out by MMPs. A basic component of the extracellular matrix is type IV collagen that is degraded by MMP-2 and MMP-9 [Wu et al, 2005]. These results are consistent with previous reports that SFN suppresses metastasis through the COX-2/MMP-2/9 pathway [Shan et al, 2013].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have suggested COX-2 as an important factor in gastric carcinoma associated with Helicobacter pylori infection (7,53), and its roles in the diseases caused by obligate intracellular bacteria of Chlamydia species and pathogenic spirochetes of Borrelia species have begun to be elucidated only recently (1,18,28). Although the status of COX isozymes in EC infected with typhus rickettsiae is currently under investigation, evidence derived from the presented data and earlier observations (48,50) suggest significant increases in the production of the major endothelial prostaglandins PGE 2 and PGI 2 during infection and implicate COX-2 and its reaction metabolites as having an integral role in the pathophysiology of rickettsial diseases.…”
Section: Discussionmentioning
confidence: 99%